Prototipo de máquina trituradora para envases plásticos pos consumo par la fabricación de hojuelas. (2021)
The present project is presented to build a prototype of a post-consumer plastic container shredder machine for the manufacture of flakes, to solve the excess volume of plastic waste that is generated, it should be noted that this prototype was specifically designed for academic reasons and not for material production purposes, since the measurements and analysis carried out with the material obtained will only be for research and projects of the UAN, Tunja headquarters.